A motor rally across Transbaikalia - Елена Григорьева; Анастасия Репина (Проект Байкал)
A motor rally across Transbaikalia was held 5-11 July 2022 by the crew consisting of Anastasia Repina, Elena Grigoryeva and Anna Loginova. The aim of the rally was small towns of the region, participation in the festival of these towns, author’s supervision of the implementation of the projects by the Siberian Laboratory of Urbanistics, several places of interest and personal reasons.